Effect of magnetite on anaerobic digestion treating saline wastewater: Methane production, biomass aggregation and microbial community dynamics. (December 2021) - Ma, Kaili; Cao, Zhiguo; Cui, Yanrui; Chen, Tingting; Shan, Shijie; Shi, Yuyang; Wang, Wei; Lv, Jinghua
Graphical abstract: Highlights: Magnetite promoted the methane yield by 16.5%-36.3% at 0.5–2% salinities. High salinity stimulated the accumulation of hydrogenotrophic methanogens. Magnetite enriched the co-occurrence patterns among microorganisms. The roles of magnetite in DIET pathway varied at different salinities. Abstract: In this study, the effect of magnetite amendment on anaerobic digestion was investigated at three increasing salinity levels (0.5%, 1% and 2% NaCl). The amendment of magnetite enhanced the methane yield by 36.3%, 33.3% and 16.5% at low salinity (0.5% NaCl) and high salinity (1% and 2% NaCl), respectively. Meanwhile, a larger proportion of granules was obtained in the magnetite amended reactor (48.05% vs 33.16% at the end of operation). Microbial analysis suggested magnetite could induce more methanogenesis partnerships between hydrogenotrophic methanogens and syntrophic bacteria. Methanosaeta and Methanocorpusculum were the alternating dominant methanogens at low salinity and high salinity. While Streptococcus and Mesotoga were two prevalent bacteria that showed totally different transition tendency in two reactors. Additionally, the supplement of magnetite could relieve the suppression of methanogenesis-related gene expression caused by salinity, thus facilitated the higher methane production.